Local museum, national history: curating Shanghai's history in the context of a changing China (1994–2018). Issue 4 (3rd April 2021) - Pozzi, Laura
ABSTRACT: The Chinese Communist Party (CCP) has traditionally exerted a profound influence over the historical narrative presented by museums located in the People's Republic of China (PRC). Nevertheless, it has been argued that, since the market reforms of the 1990s, provincial and municipal museums have partially managed to eschew national narratives in favour of focusing on local history. This article examines how curatorial practices used to present the local history have changed since the 1990s by analysing three permanent exhibitions organised by the Shanghai History Museum (SHM), the oldest local history museum in China. These three exhibitions, which were opened in 1994, 2001 and 2018, adopted remarkably different approaches to the representation of Shanghai's colonial past. This article shows how the approach taken by curators has fluctuated over the last thirty years to cater to the CCP's contemporary political needs by analysing the politics and poetics of the SHM's three exhibitions. Particular attention is paid to the resurgence of the national revolutionary narrative visible in the most recent exhibition.